PENGARUH MEKANISME CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Rendy Irawan Yunizar; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
This study aims to determine the impact of board size, the proportion of independent board, audit committee, board meetings, audit committee meetings, block holder ownership of the company's financial perfomance (RETURN ON ASSET)The population of this study are the entire manufacturing companies listed in Indonesia Stock Exchange in the period 2011-2012. This study is as much as 122 companies. Sampling was done using purposive sampling techniqueThese result of the study indicate that board size, the proportion of independent board, audit committee, board meetings, block holder ownership give significantly affect the company's financial performance. while meeting the audit committee doesn’t have a significant effect on the company fiancial perfomance